Green Lynx Spider, Peucetia viridans (Hentz) (Arachnida: Araneae: Oxyopidae) - Howard V. Weems, Jr.; W. H. Whitcomb (EDIS)
In Florida, the green lynx spider, Peucetia viridans (Hentz), is the spider most often received for identification by Division of Plant Industry entomologists. It is a conspicuous, large, bright green spider found on many kinds of shrublike plants throughout the southern United States and is the largest North American lynx spider. Although it is common throughout Florida and aggressively attacks its insect prey, it very seldom bites humans. While its bite is of little concern to humans, the green lynx spider is of interest because of its potential use in agricultural pest management. This document is EENY-249 (originally published as DPI Entomology Circular 181), one of a series of Featured Creatures from the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: November, 2001.